Computational Demonstration of Isomer- and Spin-State-Dependent Charge Transport in Molecular Junctions Composed of Charge-Neutral Iron(Ii) Spin-Crossover Complexes - Cardenas-Jiron, G; Montenegro-Pohlhammer, N (Royal Society of Chemistry, 2023)
Chemistry offers a multitude of opportunities towards harnessing functional molecular materials with application propensity. One emerging area of interest is molecular spintronics, in which charge and spin degrees of freedom have been used to achieve power-efficient device architectures. Herein, we show that, with the aid of state-of-the-art quantum chemical calculations on designer molecular junctions, the conductance and spin filtering capabilities are molecular structure-dependent. As inferred from the calculations, structural control over the transport can be achieved by changing the position of the thiomethyl (SMe) anchoring groups for Au(111) electrodes in a set of isomeric 2,2′-bipyridine-based metal coordinating ligand entities L1 and L2. The computational studies on heteroleptic iron(ii) coordination complexes (1 and 2) composed of L1 and L2 reveal that switching the spin-state of the iron(ii) centers, from the low-spin (LS) to high-spin (HS) state, by means of an external electric field stimulus, could, in theory, be performed. Such switching, known as spin-crossover (SCO), renders charge transport through single-molecule junctions of 1 and 2 spin-state-dependent, and the HS junctions are more conductive than the LS junctions for both complexes. Additionally, the LS and HS junctions based on complex 1 are more conductive than those featuring complex 2. Moreover, it is predicted that the spin filtering efficiency (SFE) of the HS junctions strongly depends on the bridging complex geometry, with 1 showing a voltage-dependent SFE, whereas 2 exhibits an SFE of practically 100% over all the studied voltage range. To be pragmatic towards applications, the ligands L1 and L2 and complex 1 have been successfully synthesized, and the spin-state switching propensity of 1 in the bulk state has been elucidated. The results shown in this study might lead to the synthesis and characterization of isomeric SCO complexes with tuneable spin-state switching and charge transport properties. © 2023 The Royal Society of Chemistry.